Transforming Barasuara's “Guna Manusia” into brass band adaptation and sociocultural impact - Ganang Dwi Asmoro; Agam Maha Putra Alhakim (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
This study examines transforming Barasuara's "Guna Manusia" from a folk-rock song into a brass band arrangement. It analyzes its cultural and sociological ramifications using Pierre Bourdieu's theory of cultural reproduction. The project aims to investigate the impact of song adaptation on audience perception, involvement, and awareness of environmental issues. The research utilizes a comprehensive technique that combines descriptive analysis and literature review. The process of descriptive analysis entails the examination of YouTube videos showcasing both the original and brass band renditions of "Guna Manusia" to comprehend the musical alterations and gauge the audience's reactions. A literature review is placed on findings within appropriate theoretical frameworks and examines prior research on music adaptation and cultural replication. The analysis demonstrates that by converting "Guna Manusia" into a brass band arrangement, its cultural importance is enhanced, and its accessibility is broadened to a broad spectrum of audiences. Descriptive analysis reveals that the brass band adaption successfully communicates the song's environmental message through instrumental expression. Bourdieu's theory demonstrates how cultural reproduction impacts the adaptation process and affects the audience's reception. The study highlights the educational and societal significance of employing music to promote environmental advocacy. It showcases how Barasuara's rendition of "Guna Manusia" actively helps increase awareness and encourage transformative change within society. The research offers unique insights into the profound impact of music and its role in tackling urgent social problems.